Designing Chatbot Interface to Accelerate Services at Disdukcapil Salatiga - Sheviana, Laela Sheviana; Cahyono, Ariya Dwika (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Managing population documents such as lost or damaged ID cards (KTP) and Family Cards (KK) remains a challenge for the public due to complex procedures, lengthy processing times, and limited access to information. This study aims to design a chatbot interface to simplify the document management process using a Design Thinking approach focused on user needs. Design Thinking consists of five stages: Empathize (identifying user problems), Define (formulating the core issues), Ideate (generating solution ideas), Prototype (creating initial designs), and Test (evaluating the solution). The prototype was tested on 37 respondents to assess its quality. The analysis results show that the average score for all statements ranged between 3 and 4, indicating positive feedback on the design. All items were validated with an r-count value > 0.3, with the highest value being 0.864, while the reliability test produced a Cronbach’s Alpha of 0.863, demonstrating excellent internal consistency. Overall, the chatbot was considered effective, user-friendly, and capable of supporting digital transformation at the Civil Registry Office (Disdukcapil). The trial also indicated a potential increase in user satisfaction of up to 85% and a 60% improvement in information retrieval efficiency compared to conventional methods. These findings suggest the proposed solution as a viable digital alternative to accelerate services, reduce queues, and enhance transparency and public satisfaction.